Macropore-assisted electrolyte transfer inside binder-free templated carbon xerogels as carbon electrode for electric double layer capacitors - Kraiwattanawong, Kriangsak (My University, 2020)
Capacitive performance of electric double layer capacitors is influenced by specific surface area, while pore structure also promotes electrolyte transfer inside a carbon electrode. Organic electrolytes require macropores, whereas aqueous electrolytes operate best using mesopores for electrolyte transfer. Templated carbon xerogels (TCXs) were prepared from resorcinol and formaldehyde with cotton fibers as a hard template containing macropores, mesopores and micropores as the carbon electrode. Results suggested that macropores (>50 nm) were contiguously created and connected with mesopore diameters (2–50 nm), leading to convenient ion transport inside the TCXs. Vacuum drying formed sponge-like carbon xerogels that permitted electrolyte transfer. Despite the insignificant change of porous properties, TCXs possessing sponge-like carbon xerogels showed increased capacitance values from 137 F/g to 317 F/g at 200 mA/g in a three-electrode system as a result of macropore-assisted electrolyte transfer in aqueous electrolytes.
Keywords: Aqueous electrolyte; Electric double layer; Macropore-assisted electrolyte transfer; Templated carbon xerogels; Vacuum drying